Improvement of UD Manjur Makmur's Business through Training and Assistance in the Application of Sari Drink Product Packaging: Peningkatan Usaha UD Manjur Makmur melalui Pelatihan dan Pendampingan Penerapan Kemasan Produk Minuman Sari - Anita Wulandari; Dian Setiya Widodo; Wahyu Kanti Dwi Cahyani (Yayasan Ahmar Cendekia Indonesia, 2022)
Noni juice is a fermented beverage that is in great demand. Noni juice is a supplement drink for the human body. Noni plant is also known as a medicinal plant. This plant is a shrub native to Tahiti and Hawaii. Noni fruit is efficacious for treating several degenerative diseases such as cancer, tumors, and diabetes. Currently, there are many products that do not have good and attractive packaging so that they are difficult to sell in the market or are not in demand by consumers, especially beverage products. Therefore, the purpose of holding this activity is This community service is to provide assistance and training in the application of product packaging noni juice drink to UD Manjur Makmur partners. The method used is the transfer of knowledge related to the design of attractive packaging labels to business owners. The result of this activity is that partners have additional knowledge related to packaging their products so that they can be better and more attractive and able to make good packaging labels that are easily understood by consumers. Meanwhile, the positive impact that occurred after this activity was carried out was that partners were able to produce higher quality noni juice products. Abstrak Minuman sari buah mengkudu merupakan minuman yang telah di fermenstasikan yang banyak diminati. Sari buah mengkudu merupakan minuman suplemen tubuh manusia. Tanaman mengkudu dikenal juga sebagai tanaman obat. Tanaman ini merupakan tumbuhan perdu yang berasal dari daerah Tahiti dan Hawaii. Buah mengkudu berkhasiat untuk mengobati beberapa penyakit degeneratif seperti kanker, tumor, dan diabetes. Saat ini banyak produk‐produk yang tidak memiliki kemasan yang baik dan menarik sehingga sulit laku dipasaran atau tidak diminati oleh konsumen terutama produk minuman, konsumen saat ini sudah dapat membedakan mana produk yang baik dan mana produk yang tidak baik tentunya dilihat dari kemasan yang digunakan. Oleh karena itu, tujuan dari diadakannya kegiatan pengabdian masyarakat ini adalah memberikan pendampingan dan pelatihan penerapan kemasan produk minuman sari buah mengkudu kepada mitra UD Manjur Makmur. Metode yang digunakan adalah transfer ilmu pengetahuan terkait dengan desain lebel pengemasan yang menarik kepada pemilik usaha. Hasil dari kegiatan ini adalah mitra memiliki tambahan pengetahuan terkait pengemasan produknya agar lebih baik dan menarik serta mampu membuat lebel kemasan yang baik dan mudah dipahami oleh konsumen. Sementara, dampak positif yang terjadi setelah dilakukan kegiatan ini adalah mitra mampu menghasilkan produk minuman sari mengkudu yang lebih berkualitas